Chosen capital : the Jewish encounter with American capitalism - Kobrin, Rebecca (Rutgers University Press, 2012)
At what moments and in what ways did Jews play a central role in American capitalism? This volume addresses this question head-on by exploring Jews' impact on American capitalism as both its architects - through their participation in specific industries - and as its most vocal critics through their support of unionism and radical political movements. Essays are contributed by a variety of scholars.